Efficiency of Malaysia stock index futures market - Ng, Chen Wai (2005)
The efficiency of stock index futures market is an important research question, given the rapid growth in such markets and their roles in the risk transference, information processing and forward pricing. This study employs weak form efficiency and semi strong form efficiency to test the market efficiency. In the case of weak form efficiency, the long-run and short-run efficiency are examine using cointegration approach and vector error correction model respectively. In many respects, the testing of semi strong form efficiency is of greatest significance to market participants, as it asks the relevant and important question of: do futures prices fully reflect all relevant publicly available information? This study used two methods for testing the semi strong form efficiency. Each of the methods is concerned with testing the projecting quality of stock index futures prices. The first approach is the forecast error approach and the second is the social loss approach. In the case of weak form efficiency, the result shows spot and futures prices are cointegrated and that this two series are clearly /(1). This means that there was evidence for the stock index futures market to exhibit long run efficiency. Meanwhile, the vector error correction model (VECM) employed that used to examine short run dynamics shows that there are deviations between futures prices and spot prices in the short run. This result also provides supporting evidence that this deviation from the short run mean can be lead back to long run convergence. In the case of testing the semi strong form efficiency, the results of the forecast error approach shows the efficient markets hypothesis (EMH) is rejected. This means that this market is inefficient or that there exists a non-zero risk premium in the stock index futures market. Finally, the results of the social loss approach employed also once again indicate that the null hypothesis of market efficiency is rejected. In other words, we can conclude that the stock index futures market does not process information efficiently. This finding has great implications to the users of this market.